Idraparinux or idrabiotaparinux for long-term venous thromboembolism treatment: a systematic review and meta-analysis of randomized controlled trials. - Yanzhi Song; Xiaodong Li; Settipalli Pavithra; Dong Li (PLoS ONE)
Background Venous thromboembolism (VTE) is a prevalent disease with potential serious consequences. Idraparinux and idrabiotaparinux are two kinds of long-acting pentasaccharides. Evidence has shown that idraparinux and idrabiotaparinux are effective anticoagulants. However, up to now, there is no consensus on whether they are better than other anticoagulation methods for long-term VTE treatment. Objective To evaluate the effect of idraparinux or idrabiotaparinux versus other anticoagulation methods for long-term VTE treatment. Methods We searched Cochrane Central Register of Controlled Trials, PubMed, Embase, Web of science, clinical trial registry web sites (clinical trials,WHO clinical trial registry), Googlescholar, PubMed related articles and companies' web sites electronically up to Dec 30(th), 2012 and manually searched the reference lists and conference proceedings. Only randomized controlled trial (RCT) involving adult patients comparing idraparinux and/or idrabiotaparinux versus other anticoagulation methods for long-term VTE treatment was included. Two reviewers evaluated the studies and extracted data independently. Pooled risk ratios (RRs) were calculated as outcome measures and Revman 5.2 software was used to analyze data. Our primary efficacy and safety outcomes were the recurrent VTE and major bleeding rates. Results We included four RCTs and involved 8584 participants on idraparinux or idrabiotaparinux versus standard warfarin for VTE treatment from 9364 references. We did not perform meta-analysis on the VTE rate because of the significant heterogeneity. We used the fixed effect model to analyze the safety outcomes and demonstrated that idraparinux or idrabiotaparinux decreased major bleeding rate significantly (RR 0.73, 95% CI 0.54 to 0.98, P = 0.04) but had a trend to increase the all cause mortality (RR 1.26, 95% CI 1.00 to 1.57, P = 0.05) compared with warfarin. Conclusions Until now there is not sufficient evidence to clarify whether idraparinux or idrabiotaparinux is as effective and safe as the standard warfarin treatment for VTE treatment.